Curcumin and carvacrol co-loaded zein nanoparticles: Comprehensive preparation and assessment of biological activities in pest control - Proença, Patricia Luiza de Freitas [UNESP]; Campos, Estefânia Vangelie Ramos [UNESP]; Costa, Tais Germano; de Lima, Renata; Preisler, Ana Cristina; de Oliveira, Halley Caixeta; da Rocha, Claudiane Martins [UNESP]; de Andrade, Daniel Junior [UNESP]; Goncalves, Kelly Cristina [UNESP]; Polanczyk, Ricardo Antonio [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2024)
To address the escalating global demand for food production, it is imperative to minimize agricultural losses caused by pests, accounting for up to 40 % of the substantial worldwide losses of 70 billion USD. While conventional pesticides raise environmental concerns, environmentally friendly alternatives like curcumin and carvacrol face low biological activity due to their low solubility and premature degradation in environmental conditions, that is, degradation can occur due to solar radiation, high temperature, etc., before the active ingredients can exert its full potential. This study introduces zein-based nanocarriers encapsulating curcumin and carvacrol, exhibiting favorable characteristics. Cytotoxicity tests indicate approximately 60% viability for fibroblast cell lines compared to 20% for keratinocyte cell lines. The nanoencapsulated compounds exhibit promising biological activity against soybean pests, mites, and caterpillars, without causing phytotoxicity. Tetranychus urticae mortality rates reach 77.1 ± 11.5 %, and nanoencapsulated ingredients demonstrate higher repellency (61.1 ± 8.8%) than emulsified ones (51.1 ± 5.4 %). Nanoencapsulated ingredients exhibit significantly higher mortality rates for Spodoptera cosmioides and Spodoptera eridania, underscoring the potential of nanoencapsulation in bolstering bioactivity against specific pests and promoting sustainable agricultural practices.
Keywords: Acaricidal effect; Crop protection; Insecticides activity; Nanotechnology; Nature-base solutions